UDK 541.64:661.18 ANALYSIS OF HYDROXYBENZENE-METHANAL OLIGOMERS USING ¹H NMR SPECTROSCOPY METHODS - Umarov, Sherali; Ismailov, Rovshan (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2025)
The chemical structure of oligomers synthesized based on hydroxybenzene-methanal and 2,5-furandione at different ratios and temperature ranges was studied using quantitative NMR spectroscopy methods. In addition to methylene bridges and simple ether bonds between hydroxybenzene rings in hydroxybenzene-methanal resins, the formation of structural groups based on 2,5-furandione, as well as macromolecular transformations and the presence of fragmentary bonds, were observed. The mechanism of the polycondensation process of hydroxybenzene and methanal in an alkaline medium was investigated. Structural and functional differences in the composition of oligomers synthesized from hydroxybenzene-methanal and 2,5-furandione were identified.